2008
DOI: 10.1309/cc6791dff20qpcx3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Oleander Poisoning by Digoxin III, a New Digoxin Assay

Abstract: We studied the potential for detecting oleander with a new immunoassay (Digoxin III, Abbott Laboratories, Abbott Park, IL) by comparing results with those from the fluorescence polarization immunoassay (FPIA) and Digoxin II assay (Abbott). In aliquots of drug-free serum pools supplemented with pure oleandrin or oleander extract, we observed apparent digoxin values using all 3 immunoassays, but values obtained by the Digoxin III were higher than obtained by the other assays. We also observed significant apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Each of the digoxin immunoassays tested in this study demonstrated significant cross-reactivity for convallatoxin, the major cardiac glycoside in lily of the valley, at concentrations in and below the reported range of in vivo Convallaria toxicity 5-7 . Cross-reactivity of older generation digoxin immunoassays for oleandrin has been previously demonstrated 10-12 and our findings extend these observations to common assays in current use. The degree of cross-reactivity varied among the individual assays and cross-reactivity for oleandrin did not correlate with that of convallatoxin.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Each of the digoxin immunoassays tested in this study demonstrated significant cross-reactivity for convallatoxin, the major cardiac glycoside in lily of the valley, at concentrations in and below the reported range of in vivo Convallaria toxicity 5-7 . Cross-reactivity of older generation digoxin immunoassays for oleandrin has been previously demonstrated 10-12 and our findings extend these observations to common assays in current use. The degree of cross-reactivity varied among the individual assays and cross-reactivity for oleandrin did not correlate with that of convallatoxin.…”
Section: Discussionsupporting
confidence: 84%
“…1), we hypothesized that commonly available digoxin immunoassays would cross-react with convallatoxin. Previous studies have demonstrated cross-reactivity of older digoxin immunoassays for botanical digitoxin 9 and oleandrin, the major cardiac glycoside in Nerium oleander 10-12 . In this study, we tested a panel of five digoxin immunoassays in current clinical use for cross-reactivity to convallatoxin and oleandrin.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are derived from the structural and chemical similarities between the yellow oleander cardenolide-oleandrin and digitalis cardenolides derived from foxglove 5. These chemical similarities allow for some cross reactivity and detection by immunoassays utilised for measuring serum digoxin levels, with variable sensitivities 6 7. Ingestion of any part of the plant can result in poisoning with variable pharmacokinetics depending on the cardiac glycoside concentration of the different parts of the plant and the time following ingestion 3 5.…”
Section: Discussionmentioning
confidence: 99%
“…The more recently introduced Digoxin III assay marketed by Abbott Laboratories has similar sensitivity as the FPIA assay for detecting oleander poisoning [38] . Although the digoxin immunoassay with high cross -reactivity against oleandrin such as Digoxin III or Dimension Vista digoxin assay can be used for the indirect detection of apparent digoxin concentration in a suspected oleander poisoning, for a defi nite diagnosis, the presence of oleandrin, the toxic glycoside in oleander in blood, should be confi rmed using highperformance liquid chromatography and mass spectrometry (HPLC/MS), a direct analytical technique for detection of oleandrin in blood [39] .…”
Section: Oleander Containing Herbs and Digoxin Immunoassaysmentioning
confidence: 99%